Grundtvigs forfatterskab i dansk litteraturhistorieskrivning - Dahl, Per (Grundtvig-studier, 2010)
Grundtvigs forfatterskab i dansk litteraturhistorieskrivning[Grundtvig’s works in Danish historiography]By Per Dahl The essay discusses the most important Danish literary histories written between 1881 and 2008 and their representation of the writings of N. F. S. Grundtvig (1783-1872). In 1881 Frederik Winkel Horn wrote the first updated history of Danish literature including the 19th century. The extensive chapter on Grundtvig deals with his conception of Nordic and Christian education and culture. From an aesthetic point of view, says Horn, Grundtvig’s poetry does not meet academic criteria. Nevertheless his best poems and prose writings are profoundly thrilling by virtue of strength of mind and poignancy. Five years later an evaluation by Peter Hansen was more reserved, but he appreciated Grundtvig’s hymns. Vilhelm Andersen’s chapter on Grundtvig in Illustreret Dansk Litteraturhistorie (1924) is evaluated as the most complex study in Grundtvig and his collected writings. This lengthy chapter (of some 75 pages) expresses an exclusively literary point of view.The structural unity of Grundtvig’s works, says Andersen, is based on the basic dichotomy between life and death and Grundtvig’s inner experience, resulting in a decisive turning point where he sees life bom out of darkness.To Andersen the most important texts are the long poem Nyaars-Morgen (The Morning of New Year’s Day) and the hymn De Levendes Land (The Land o f the Living), both written in 1824 - a climax and a turning point in Grundtvig’s poetry. Up to 1824 Andersen’s biographical approach and view of the phases and motives for Grundtvig’s writings are in accordance with his inner development. The period after 1824 is evaluated as a phase of realization of his ideas. Andersen’s exposition in Illustreret Dansk Litteraturhistorie inaugurated a process of canonization of the above-mentioned texts. In 1958 F. J. Billeskov Jansen (Danmarks Digtekunst) stiffened the literary demands in keeping with his comparative point of view. Martin Zerlang’s chapter on Grundtvig in Dansk litteraturhistorie (vol. 5, 1984) as well as Johnny Kondrup’s chapter in Hovedsporet. Dansk litteraturs historie (2005) and Sune Auken’s in Dansk litteraturs historie (vol. 2, 2008) confirm the canonical status of Nyaars-Morgen. Finally the essay discusses problems concerning canonization and representation of works when writing literary history.